Analisis Pengaruh Corporate Social Responsibility Dan Variabel Makro Ekonomi Terhadap Kinerja Keuangan Dan Harga Saham Perusahaan Pertambangan Di Indonesia - Shindu Hargo Dedali (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2019)
The purpose of this research is to test the influence of corporate social responsibility, macro economic variables, and financial performance on the stock prices of Indonesia mining companies, the influence of corporate social responsibility and macroeconomic variables on financial performance of Indonesia mining companies, and the influence of corporate social responsibility and macro economic variables on the stock prices through financial performance as intervening variable.The samples size of this research is 17 Mining corporations in Indonesia Stock Exchange.Using the panel data regression and path analysis. The results show that the corporate social responsibility, macroeconomic variables, and financial performance have significant influences on the stock prices of Indonesia Mining Industries. The corporate social responsibility and macroeconomic variables have significant influencesonÂ  financial performance.With path analysis, the result show the corporate social responsibility and macro economic variables do not have significant influence on the stock prices of Indonesia mining companies with financial performance as intervening variable.